ANALISIS MEKANISME MANAJEMEN RISIKO PEMBIAYAAN GADAI EMAS PADA PEGADAIAN SYARIAH AR. HAKIM MEDAN - Khairina, Dina; Kurniawan, Rahmat (JURNAL ILMIAH EDUNOMIKA, 2024)
Rahn (gold) pawn products in Islamic pawnshops are increasingly in demand by the public, so risk management is the most effective process or strategy to overcome or minimize the risks that occur or will occur. This research aims to find out the risk management mechanism for gold pawning at the Islamic Pawnshop AR Hakim Medan Branch Office, the method used in this research is descriptive qualitative research where data collection uses observation techniques, interviews, and documentation studies. In this study, researchers interviewed informants, namely branch leaders, estimators, and cashiers. Pegadaian Syariah Branch Office AR Hakim Medan. The results showed that the risk management mechanism for gold pawning at Pegadaian Syariah AR Hakim Medan Branch Office has been running quite well, this is evidenced by the results of interviews and observations. The risk management mechanism for gold pawning at the Pawnshop Syariah Branch Office AR Hakim Medan applies several stages, namely, risk identification, risk measurement, risk management and risk control and supervision. These stages can anticipate and minimize the risks that occur in gold pawning at the Pawnshop Syariah AR Hakim Medan Branch Office such as the risk of counterfeit gold fraud, bad credit, gold price fluctuations, too high gold valuations. Keywords: Pawnshop, Gold pawn, Risk management